Pelaku UMKM Industri Kreatif di Jawa Timur Sadar Pentingnya Inovasi Dalam Menghadapi Disrupsi Teknologi - Purnomo Sidi, Agus; Citaningtyas Ari Kadi , Dian; Santoso, Risa (RELASI : JURNAL EKONOMI, 2024)
This research was conducted to find the relationship between Business Resilience, Innovation, and Technological Literacy on the Performance of MSMEs in the East Java region, especially in the creative sector. Technological disruption has changed behavior in meeting consumer needs. A response is needed from MSMEs to face changes in consumer behavior. This changing consumer behavior can affect the performance of MSMEs. MSMEs that can adapt to innovation are expected to maintain business performance. On the other hand, MSMEs also need to consider the business resilience and technological literacy of their human resources in maintaining MSME performance. This research was conducted using regression analysis involving 100 business actors in the creative sector in the East Java region. From the results of this study, it was found that Business Resilience, Innovation, and Technology Literacy influenced Business Performance. Innovation is the key to an important role in maintaining and improving business performance.